A implementação de políticas públicas voltadas ao artesanato na Paraíba: análise do programa Paraíba em suas mãos - Moraes Sobrinho, João (2014)
The implementation of public policies is the phase of the policy cycle regarded with the operationalization of the decisions and policies, when they are no longer just intentions and turn into concrete actions. Several studies, since the 1970s, have been conducted in order to analyze the various factors responsible for the success or failure of government programs. This study examined the process of implementing of public policies named Programa de Artesanato Paraibano (a handcraft program), with the goal of identifies several elements that affect and influence the implementation of program activities. The implementation stage is considered a crucial step for the success or failure of a program and is required to be properly analyzed because the results of certain policies often differ from those projected in the stage of policy formulation. It is believed that this work will provide to program managers a wider understanding of various elements that influence and affect the operation of the developed and implemented public policies, influencing its effectiveness. This work was based on two theoretical models of implementation of public policies that have been adapted and agglutinated, because each singly was not considered enough to cover and explain all the dynamic of the process analyzed. The research, a descriptive case study, was conducted under the qualitative perspective. The data for the study were obtained through desk research, the legal and regulatory aspects of the program were analyzed and field research, in which the actors implementers and beneficiaries of the program underwent semistructured interviews. Data analysis used the technique of content analysis. Results indicate that the dynamic deployment of Paraiba craft sector is influenced by elements of the institutional political context, especially a normative consolidation yet to consolidate and influence of transitions between governments, which generates resource constraints and variables and security to stakeholders. Notwithstanding the events listed, the program has significant results that favored a higher level of training of handcraftsmen, fairs and access to regional and national events and income gains. This latter aspect, although relevant, is still considered insufficient by local handcraftsmen. We conclude that the dynamics of implementation of public policies within the analyzed program is influenced by technical, political and institutional factors and events that act as elements that affect the results of the implementation of the policy itself.